The phonetics and phonology of Xhosa demonstratives : a non-linear approach - Maxela, Thandiwe(Thandiwe Ozinah) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1995.